Item Analysis of Multiple-Choice Questions in Pharmacology in an Indian Medical School - Adiga, Manoor Narasimha Sachidananda; Acharya, Swathi; Holla, Rajendra (Journal of Health and Allied Sciences NU, 2021)
Introduction Student assessment by multiple-choice questions (MCQs) is an integral part of student evaluation in medicine. The medical teacher should be trained to construct an item with proper stem and valid options. Periodic item analyses will make the process of assessment more meaningful. Hence, we conducted the study to analyze MCQs (item analysis) tested on a batch of MBBS students in pharmacology in their three internal assessment examinations.Methods The study was conducted in the Department of Pharmacology of a medical college in Mangaluru on 150 students. The MCQs of the three internal assessment examinations (20 each) respectively were analyzed. We analyzed each question for difficulty index (DI), discrimination index (DsI), and distracter efficacy or functionality and expressed the percentage results.Results The DI was in an acceptable range of 60, 75, and 90%, respectively, in the three internal assessments. The percentage of “too difficult” questions was 10, 20, and 10% and the average DsI was 0.32 ± 0.04, 0.28 ± 0.02, and 0.26 ± 0.02, respectively. In the second and third internal assessments, 95% of questions had functional distracters, while in the first internal assessment, only 60% of questions had functional distracters.Conclusion We conclude from our study that even though the items (MCQs) framed for the internal assessments were in the acceptable range of quality in terms of the parameters assessed, we must improve MCQ’s construction in selecting distracters in some topics.
Keywords: item analysis; MCQs; difficulty index; discrimination index